Análise da implantação do Programa Mais Médicos no Município de Breves – Estado do Pará - GUIMARÃES, Daniel Silva (Universidade Federal do Pará, 2019)
The work deals with the evaluation of the implementation of the Federal Government's program "More doctors" in the municipality of Breves, State of Para. The aim of the dissertation is to analyze the impacts caused by the PMM in Basic Health Units of the municipality of Breves and local development health sector. Highlights three areas: i.) Strategy emergency hiring doctors, ii) number of places Expansion for medical courses and residency and iii) Infrastructure of Basic Health Units used in the methodological approach to quantitative research and qualitative and literature review. The data collection instruments were open questionnaire and consultation with secondary databases, electronic and printed media, books, magazines, papers. The results show the improvement in the SUS considering quantitative data, the increase in the number of doctors, significant investment in construction and UBS expansion and rising vacancies in medicine and medical residency programs. However, problems are still evident in the health sector. According to the proposal of the PMM structural changes must implement increasingly comprehensive improvements in the medium and long term, setting the goal of a ratio of 2.7 doctors per thousand inhabitants, providing inputs for a service with higher quality in public service in health